Gender Differences in Suicidal and Self-Harming Responses to Esketamine: A Real-World Retrospective Study - Martiadis, Vassilis; Raffone, Fabiola; Atripaldi, Danilo; Testa, Serena; Giunnelli, Paolo; Cerlino, Rita; Russo, Manlio; Martini, Azzurra; Pessina, Enrico; Cattaneo, Carlo Ignazio; De Berardis, Domenico (Current Neuropharmacology, 2025)
<span class=
Keywords: suicide